Tinjauan Penerapan Pungutan Pajak dan Zakat Menurut Konsep Ekonomi Islam di Indonesia - Nurul Ichsan Hasan (Universitas Muhammadiyah Purwokerto (UMP), 2018)
This paper deals with the source of the country's sources of income in the modern era it is more known for its tax obtained from the community for the purposes of the State for the prosperity of the community. Taxes in Islam was taught by the Prophet Muhammad SAW certainly different provisions and type so that it provides insight for us to assess how the difference in the terms and conditions of the religion taught in the modern era of the levy by the State to the people so that we can assess, read and take heed and which one is better and can be applied in the life of a country. The purpose of this paper is to expose about the wealth tax, income tax, (zakat), a land tax (kharaj), tax farming (usr), a protection tax (Jizya), a tax customs import tax, (ushur), the spoils of war (ghanimah and fa'i) along with the conditions that exist in tenet of Islam.